(untitled) (Acta Scientiarum. Biological Sciences, 2025)
This study analyzes the demographic profiles of HIV patients in Southern Brazil from 2011 to 2021, with a focus on the states of Rio Grande do Sul, Santa Catarina, and Paraná, using data from the DATASUS system. A total of 87,025 diagnosed cases were reported, with Rio Grande do Sul accounting for the highest proportion (48%), followed by Santa Catarina (27%) and Paraná (25%). Linear regression analysis revealed a general decline in HIV notifications across all three states, suggesting improvements in public health measures. Gender analysis indicated a higher prevalence among men (62%), and a greater reduction in cases among women over the decade. The data also highlighted disparities in HIV incidence related to race/ethnicity and age, with the white population showing the highest number of notifications and the 20-49 age group being the most affected. Educational level analysis pointed to a significant number of cases among individuals with elementary education. Our findings emphasize the importance of tailored public health strategies to address the diverse factors influencing HIV transmission. Continued efforts in prevention, accurate data reporting, and targeted interventions are crucial to sustaining the downward trend and addressing the specific needs of vulnerable populations.